CT 2008 : tomography confluence : an international conference on the applications of computerized tomography, Kanpur, India 15-17 February 2008 - CT 2008 (2008 : Kanpur, India); Munshi, Prabhat (Melville, NY : American Institute of Physics, 2008)
42